Silicon photonic processor of two-qubit entangling quantum logic. (17th October 2017) - Santagati, R; Silverstone, J W; Strain, M J; Sorel, M; Miki, S; Yamashita, T; Fujiwara, M; Sasaki, M; Terai, H; Tanner, M G; Natarajan, C M; Hadfield, R H; et al.
Abstract: Entanglement is a fundamental property of quantum mechanics, and is a primary resource in quantum information systems. Its manipulation remains a central challenge in the development of quantum technology. In this work, we demonstrate a device which can generate, manipulate, and analyse two-qubit entangled states, using miniature and mass-manufacturable silicon photonics. By combining four photon-pair sources with a reconfigurable six-mode interferometer, embedding a switchable entangling gate, we generate two-qubit entangled states, manipulate their entanglement, and analyse them, all in the same silicon chip. Using quantum state tomography, we show how our source can produce a range of entangled and separable states, and how our switchable controlled-Z gate operates on them, entangling them or making them separable depending on its configuration.